Infecciones gastrointestinales en el curso de infecciones respiratorias agudas en edad pediátrica - Muñoz Peralvo, Cristian Xavier (2024)
Respiratory infections are common in the pediatric population. They constitute the main reason for medical consultation and hospitalization in children under five years old. Although diarrhea is the most common symptom resulting from infection by enteric pathogens, respiratory virus infections can also present with this symptom. Objective: to describe the impact of Acute Respiratory Infections (ARIs) on the gastrointestinal tract in the pediatric age group to enhance the quality of life and prognosis of pediatric patients. Methods: This review focuses on understanding the relationship between gastrointestinal infections and acute respiratory infections in children. It employs a descriptive approach to gather and analyze detailed information, following the design of a systematic review in accordance with PRISMA guidelines. Results: Adenoviruses can cause febrile illnesses in young children, potentially leading to complications like pneumonia and multi-organ involvement. On the other hand, coronaviruses, known to cause some respiratory infections, have also been associated with diarrhea in infants and young children. Studies have shown the presence of coronavirus and adenovirus particles in feces of patients with acute gastroenteritis while concurrently experiencing a respiratory infection. Conclusion: Gastrointestinal infections during acute respiratory infections in children pose a challenge for healthcare professionals in terms of diagnosis and treatment, particularly considering the potential involvement of respiratory viruses. These viruses can cause a wide range of symptoms, from mild self-limiting illnesses to severe extrapulmonary complications.